(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The paper presents the results of a field research carried out in three international fashion schools - Polytechnic University of Milan (Italy), Iuav University of Venice (Italy) and Escola d’Art i Superior de Disseny of Alcoi (Spain) - to investigate the fashion portfolio as a tool to build the identity of its author. In the fashion system, the portfolio is an essential tool, required at every application, presented at every interview, and it is often the only element available to the evaluators for selection among different subjects. However, the theoretical reflection developed in academic research around the portfolio is still very limited and this contribution aims to fill at least part of the gap. A workshop has been designed and carried out, which the paper describes and analyses in its different phases, with the aim of simulating a part of the process of portfolio realisation and carrying out an exploratory investigation, documenting the students’ considerations, their perception of this tool, the problems encountered, the methods of realisation, the influence of the context and the relationship with the author’s identity.